The Way of Presenting Political Events in Mass Media: Interpretation of the Events at the Poland-Belarus Border Determined by the Owner of the Medium: the Media Content Analysis Method - Adamczyk, Anna (Political Preferences, 2022)
The article analyzes the media broadcasts in the evening editions of the news broadcasts on TVP and TVN (with different ownership forms) concerning the events at the Poland-Belarus border. Examined were the content, its form, visual and auditory messages. The analyzed aspects are enumerated to distinguish the broadcaster of the TV message, showing possible similarities and differences in that message. In this way, the author wanted to answer, if there is a difference in the presentation of the same political event by depending on who is the owner of the medium. As a background for the conducted research, the author presents theoretical issues concerning the mediatization of the political sphere and the agenda-setting theory.